Understanding the Influence of the Head Coach on Soccer Training Drills—An 8 Season Analysis - Steve Barrett; Matthew C. Varley; Samuel P. Hills; Mark Russell; Matt Reeves; Adam Hearn; Christopher Towlson (Applied Sciences, 2020)
Soccer players perform a variety of training drills to develop the physical, technical and tactical qualities required for match-play. The role of coaches in prescribing training suggests that players may not always meet physical targets set by conditioning staff. To quantify the physical outputs elicited by different training drill types, 183 professional soccer players were monitored over 8 seasons using Microelectromechanical Systems during normal training, yielding 65,825 drill observations [362 ± 341 observations·player−1]. Linear mixed models assessed the influence of drill type, head coach and playing position on physical output. Drills lasted ~14 min, eliciting total distances and high speed running of ~1000 m and 40 m, respectively. Conditioning drills elicited substantially greater relative high-speed running [18.8 ± 27.2 m.min−1] and Sprint [3.5 ± 9.4 m.min−1] distances than all other drill types. The proportion of training drill types used and external outputs elicited per drill were affected by the head coach. Midfielders recorded the highest total distance [77.3 ± 36.1 m.min] and PlayerLoad™ [8.29 ± 3.54] of any playing position, whilst the lowest outputs were recorded by goalkeepers. This study provides reference data for practitioners when seeking to manipulate training prescription to achieve physical output targets whilst also meeting the team’s technical and tactical objectives.